Average circular D-distance and circular D-Wiener index of K-regular graphs (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The circular  -distance between nodes of a graph   is obtained by the sum of detour  -distance and  -distance. The average circular  -distance between the nodes of a graph is the sum of average of the detour  -distance and  -distances. In this paper, we deal with the average circular  -distance between nodes of graph. We compute the relation between circular Wiener index and circular  -Wiener index of  -regular graphs. We obtained results on circular  -Wiener index of some special graphs